The ‘piston’ effect of the calf muscle pump in region of Achilles tendon - Jose Maria Pereira de Godoy*,Henrique Jose Pereira de Godoy,Ana Carolina Pereira de Godoy,Maria de Fatima Guerreiro Godoy (Innovative Journal of Medical and Health Sciences, 2019)
Aim: The aim of the current study was to highlight the ‘piston’ effect of the calf muscle pump using constriction mechanisms. Method: Working pressure variations of 27 lower limbs of 14 volunteers wearing 20/30 mmHg elastic stockings were evaluated using a balloon catheter. The balloon catheter was 4 x 5 cm in size, placed between the skin and the material of the stockings and connected to a DTX Plus TM sensor; a portable device that collects and stores pressure readings at half-second intervals. One catheter was placed in the medial region of the calf muscle and another at the insertion point of the Achilles tendon in this muscle. The volunteers were asked to walk. The paired Student t-test was utilized for statistical analysis with an alpha error of 5% considered acceptable. Result: The pressure variations were greater in the region where the Achilles tendon is inserted into the muscle than in the medial region of the calf muscle (Student t-test; p-value = 0.0006). Conclusion: At the insertion point of the Achilles tendon in the calf muscle there is a ‘piston’ effect during exercising, causing working pressure variations when contention mechanisms are used. Key words: Elastic stockings–working pressure–mechanism–piston effect